1985
DOI: 10.1176/ajp.142.6.735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of social support on stress-related changes in cholesterol level, uric acid level, and immune function in an elderly sample

Abstract: Strong social support systems, which in epidemiologic studies are associated with decreased morbidity and mortality, have been hypothesized to mitigate the harmful effects of stressful stimuli on the individual. The authors found that, among 256 healthy elderly adults, individuals with good social support systems tended to have lower serum cholesterol and uric acid levels and higher indices of immune function; these correlations were independent of age, body mass, tobacco use, alcohol intake, and degree of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In general, the available recent literature provides no evidence that the influence of perceived or received social support on cardiovascular, neuroendocrine, and/or immunity is statistically mediated by anxiety, life stress, subjective distress, or depression (Clark, 2003; Cosley et al, 2010; Hilmert et al, 2002; Lutgendorf et al, 2000, Lutgendorf et al, 2005; Marsland et al, 2007; Taylor et al, 2010). As noted earlier, this is not a recent trend (Baron et al, 1990; Kiecolt-Glaser, et al, 1991; Thomas, et al, 1985). …”
Section: The Ghosts Of Research Past and Present: Testing Psychologicmentioning
confidence: 49%
See 2 more Smart Citations
“…In general, the available recent literature provides no evidence that the influence of perceived or received social support on cardiovascular, neuroendocrine, and/or immunity is statistically mediated by anxiety, life stress, subjective distress, or depression (Clark, 2003; Cosley et al, 2010; Hilmert et al, 2002; Lutgendorf et al, 2000, Lutgendorf et al, 2005; Marsland et al, 2007; Taylor et al, 2010). As noted earlier, this is not a recent trend (Baron et al, 1990; Kiecolt-Glaser, et al, 1991; Thomas, et al, 1985). …”
Section: The Ghosts Of Research Past and Present: Testing Psychologicmentioning
confidence: 49%
“…There were a number of social support studies during this time period in which it was less clear if these psychological factors were viewed as confounds or mechanisms (Kirschbaum et al, 1995; Unden et al, 1991; Linden et al, 1993; Thomas et al, 1985). Nevertheless, none of these studies reported evidence that would be consistent with strong psychological mediation.…”
Section: The Ghosts Of Research Past and Present: Testing Psychologicmentioning
confidence: 99%
See 1 more Smart Citation
“…Many parents and service providers spoke about the stresses associated with integrating into Canadian society, including economic and employment difficulties. Increased stress is a risk factor for elevated cholesterol levels (Thomas et al 1985;Theorell and Akerstedt 1976). Unfortunately, many refugee families have lost their social support network through migration; they are in the process of establishing a new social network in Canada.…”
Section: Chronic Health Conditionsmentioning
confidence: 99%
“…When the patients feel inadequate social supports, their immune system functions are altered,[ 9 10 11 12 13 ] whereas when feel adequate social supports, they respond better to stressors and their immune system functions are improved. [ 14 15 ] This process is more prominent in patients with IBS because of the inflammatory background of disease.…”
Section: Introductionmentioning
confidence: 99%